2010
DOI: 10.1002/ange.200905827
|View full text |Cite
|
Sign up to set email alerts
|

Dynamers at the Solid–Liquid Interface: Controlling the Reversible Assembly/Reassembly Process between Two Highly Ordered Supramolecular Guanine Motifs

Abstract: String quartet: A dynamic assembly/reassembly process in octadecyl guanine (G) monolayers was triggered by addition of [2.2.2]cryptand, potassium picrate (K+(pic)−), and trifluoromethanesulfonic acid. The resulting structures, which alternate between a hydrogen‐bonded G ribbon and a G quartet, were monitored by STM at the solid–liquid interface on graphite (see picture).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…[6] Liposomes, [7] surfaces, [8] dynamers, [9] hybrid materials, [10,11] and mesoporous silica [12] have been used as scaffolding matrices to stabilize and to orient the anisotropic directional G-mesophases. They are reminiscent of other supramolecular pore-confined systems [13,14] or DNA-modified surfaces.…”
mentioning
confidence: 99%
“…[6] Liposomes, [7] surfaces, [8] dynamers, [9] hybrid materials, [10,11] and mesoporous silica [12] have been used as scaffolding matrices to stabilize and to orient the anisotropic directional G-mesophases. They are reminiscent of other supramolecular pore-confined systems [13,14] or DNA-modified surfaces.…”
mentioning
confidence: 99%
“…In this regard, the metal salts or metal complexes can coordinate with active building units, thus resulting in phase transformation at solid/liquid surfaces. [96] Guanine (G) is an extremely versatile building block able to self-assemble into various discrete architectures including dimers, ribbons, and macrocycles depending on its environment. [94] They found that the functionalized bipyridines can be used as scaffolds for metal complexes upon addition of a solution of a metal salt when the intermolecular distance within the non-complex monolayer is suitable.…”
Section: Coordination-driven Reversible Phase Transformationmentioning
confidence: 99%
“…[94] They found that the functionalized bipyridines can be used as scaffolds for metal complexes upon addition of a solution of a metal salt when the intermolecular distance within the non-complex monolayer is suitable. In the aforementioned report, [96] Samorì et al presented sequential STM images of a reversible adsorption/desorption process at the solid-liquid interface upon addition of potassium picrate (K + A C H T U N G T R E N N U N G (pic) À ) and its subsequent removal by [2.2.2] cryptand. In another work, Kanesato and co-workers presented an interesting phenomenon of a coordination-driven odd-even effect.…”
Section: Coordination-driven Reversible Phase Transformationmentioning
confidence: 99%
“…Counterions also play a decisive role in supramolecular interactions and lead eventually to the formation of specific supramolecular complexes [10]. However, while counterions constitute an elegant way to modify electronic properties of molecules at the liquid–solid interface, their role in 2D self-assembly has been given little attention so far, mostly because they could not be visualised by STM [1114]. …”
Section: Introductionmentioning
confidence: 99%